Literasi Digital Pada Pembelajaran Abad 21 Di Sekolah Dasar - Nopi Krisnawati; Septy Qurrotu Aini Farradhillah; Siti Mariyam; Ismaya Febrianti; Desti Setianingsih; Sofyan Iskandar; Nuur Wachid Abdul Majid; Neneng Sri Wulan (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
Education in Indonesia is undergoing a revolution towards a more advanced and innovative education. The current education system has led to a digital system and no longer uses traditional methods. This shows a change towards 21st century education. Where learning is directed to use technology. One of the technologies that can be used in learning is the media YouTube. The use of YouTube media is not only as entertainment but can also be a source of learning. The amount of information and knowledge obtained on YouTube can have a positive impact on the digital literacy movement for elementary school students. This research was conducted to analyze the use of YouTube media as a digital literacy movement in 21st century learning in elementary schools. This study uses qualitative methods and the type of research is descriptive with data collection techniques in the form of questionnaires and literature review. The results of this study using YouTube media can provide convenience to students in the learning process. In addition, YouTube media supports 21st century learning so that it can help students to face future technological challenges and YouTube media is also considered to be a driving force for digital literacy in elementary school students.